Russkii bunt - Proshkin, Alexander (Russia : NTV-Profit ; Globus Film Studio ; Canal+ ; Production Le Pont ; Roissy Films, 2000)
Historic epic drawn from two of Alexandr Pushkin's most beloved works, The Captain's Daughter and A History of Pugachev. The film opens with young cadet Pyotr Grinyov leaving for his remote encampment after Empress Catherine II has her husband Peter killed. On the rookie soldier's journey, he lends his fur coat to runaway Emelian Pugachev, who soon believes that young Pyotr is in fact Tsar Peter III. Later, at the fortress, Pyotr finds himself competing with his fellow soldiers for the attention of Masha, the gorgeous daughter of the fort's commanding officer, while Pugachev masses rebel forces against the fort.
Keywords: Fiction films